2014
DOI: 10.3329/bjch.v38i1.20022
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of Congenital Heart Disease in Children Admitted into Tertiary Care Hospitals of Sylhet: A Multicenter Study

Abstract: Objective: This study was carried out to find out the prevalence of CHD and their type among Children attended in the inpatient and out patient department of district tertiary care hospital of Sylhet. Methodology: This prospective cross sectional study was carried out in the department of Paediatrics of 4 medical college hospitals of Sylhet over a period of 1 year from January 2012 to December 2012. All children with the confirmed diagnosis of CHD with the age ranging from 1st day of life to 12 years were anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 5 publications
3
2
0
Order By: Relevance
“…Overall male female ratio of CHD was 1.5:1. This finding was similar with Sharmin et al, 4 Ibrahim et al, 12 and Hoque et al, 11 where male female ratio was 1.3:1,1.2:1 and 1.7:1 respectively.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Overall male female ratio of CHD was 1.5:1. This finding was similar with Sharmin et al, 4 Ibrahim et al, 12 and Hoque et al, 11 where male female ratio was 1.3:1,1.2:1 and 1.7:1 respectively.…”
Section: Discussionsupporting
confidence: 82%
“…This correlated with studies of Hussain et al, 13 Mollah et al 14 and Hoque et al 11 But this differs from Rahman et al, 15 and Begum et al 16 They found atrial septal defect as the commonest acyanotic lesion. This difference in observation might be due to including many adult patients by Rahman et al 15 and only preterm babies by Begum et al 16 in their studies.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Similar studies were found that 65.38% were acyanotic and 34.42% cases were cyanotic, with the commonest CHD of VSD-33.33%, ASD-16.24%, TOF-11.54%, PDA -10.68% (Hoque et al, 2014); another study based on the Department of Paediatric Cardiology at National Institute of Cardiovascular Diseases, Dhaka, found that VSD-27.2% and TOF-20.5%. A study based on neonate children aged birth to 28 weeks gestational period were found that ASD-26%, VSD-16.9%, PDA-18%, TOF-14%, PS-7.75% with asymptomatic high-risk neonates contributing to early detection of many trivial lesions [14].…”
supporting
confidence: 60%
“…It was found that, pre-existing maternal diabetes is associated with a fivefold increase in the congenital heart disease [15]. Until 2009, a study in Norway confirmed that this association of CHD and DM mothers is almost two to three fold than the non-DM mothers [16].…”
mentioning
confidence: 99%